Screening of Marine-Derived Fungi Extracts as Antioxidant, Tyrosinase Inhibitor, and Antiglycation - Muhamad Nursid; Endar Marraskuranto; Dilaika Septorini; Irmanida Batubara (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2019)
Marine-derived fungi are of great interest as new promising sources of bioactive secondary metabolites. The aim of this study was to determine the antioxidant activity, tyrosinase inhibitor and antiglycation of marine-derrived fungi collected from Kepulauan Seribu Marine National Park, Indonesia. Antioxidant screening was determined using the 1,1-diphenyl-2-picryl hydrazyl (DPPH) method. The tyrosinase inhibitor was screened using L-tyrosine substrate, while the antiglycation test was determined by the ability to inhibit the formation of advanced glycation end products (AGEs). A total of 28 marine fungi isolates had been screened for their activities. Mycelium extract of MFP 271 had the best antioxidant activity with the IC50 of 287.25 ± 50 µg/mL. Mycelium extract of MFP 277 had the best tyrosinase inhibitory activity with the IC50 of 586.42 µg/mL. The MFP 274-broth extract had the highest antiglycation activity with the IC50 value of 298.57 µg/mL. Based on the screening, the crude extracts were considered weak as antioxidant, but tyrosinase inhibitor and antiglycation activity of MFP 277 and MFP 274 are needed to investigate in depth activities.